2003
DOI: 10.1021/jf026203j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Juniperus from Ripe and Unripe Berries and Leaves and Their Antimicrobial Activity

Abstract: The composition of the essential oil from ripe and unripe berries and leaves of Juniperus oxycedrus L. ssp. oxycedrus, Juniperus phoenicea ssp. turbinata and Juniperus communis ssp. communis was analyzed by GC-MS, and microbiological assays were carried out. Samples were collected in different localities (Sardinia, Italy) and hydro distilled. The yields ranged between 2.54% +/- 0.21 (v\w dried weight) and 0.04% +/- 0.00. A total of 36 components were identified. The major compounds in the essential oils were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
6
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 16 publications
18
134
6
3
Order By: Relevance
“…Also, the yield of EOs from leaves of C. sempervirens L. obtained in this study was lower than that reported by Mazari et al (2010); Elansary et al (2012) and Amri et al (2013), and lower than the yield of EOs from cone of Tunisian C. sempervirens L. which reported by Ben Nouri et al (2015). The yield of EOs isolated from leaves of J. phoenicea L. obtained in this study was lower than that reported by Stasis et al (1996); Mazari et al (2010); Derwich et al (2010) and Amalich et al (2015), but it was relatively similar when compared to that reported by Angioni et al (2003) and Achak et al (2009). 2.…”
Section: Results and Discussion 1 Yield Of The Essential Oilssupporting
confidence: 54%
“…Also, the yield of EOs from leaves of C. sempervirens L. obtained in this study was lower than that reported by Mazari et al (2010); Elansary et al (2012) and Amri et al (2013), and lower than the yield of EOs from cone of Tunisian C. sempervirens L. which reported by Ben Nouri et al (2015). The yield of EOs isolated from leaves of J. phoenicea L. obtained in this study was lower than that reported by Stasis et al (1996); Mazari et al (2010); Derwich et al (2010) and Amalich et al (2015), but it was relatively similar when compared to that reported by Angioni et al (2003) and Achak et al (2009). 2.…”
Section: Results and Discussion 1 Yield Of The Essential Oilssupporting
confidence: 54%
“…Needles -Pinene (78%), -pinene (5%), myrcene (4%),  3 -carene (1.8%), limonene (1%), methyl citronellate (0.7%) Von Rudloff and Sood, 1969 Sabinene (48.4%), -pinene (16.5%), myrcene (3.5%), p-cymene (3.2%), limonene (2.0%), -terpinolene (1.6%) Vernin et al, 1988 -Pinene (41%), sabinene (17%), limonene (4%), terpinen-4-ol (2.7%), myrcene (2.6%), -pinene (2%) Chatzopoulou and Katsiotis, 1993 -Pinene (64%), -phellandrene (19%), myrcene (9.5%), -pinene (2.1%),  3 -carene (1.8%), limonene (1.5%), Ochocka et al, 1997 Sabinene (48.8%), -pinene (6.2%), endofenchyl acetate (5.8%) Pande and Mathela, 2000 Sabinene (40.7%), -pinene (12.5%), terpinen-4-ol (12.3%), -terpinene (3.8%), limonene (3.7%), -thujene (3.1%) Sabinene (61.1%), terpinen-4-ol (10.7%), -pinene (6.4%), -terpinene (3.3%), myrcene (2.6%), limonene (2.5%) Angioni et al, 2003 Limonene ( J. chinensis -leaves Umbelliferone † , 2-(3,4-methylenedioxyphenyl)propane-1, 3-diol, meso-secoisolariciresinol, 3,4-methylenedioxy-3',4'-dimethoxylignan-9',9-olide, hibalactone, isohibalactone, 7-oxohinokinin, 7-hydroxyhinokinin, 7-acetyloxyhinokinin, (+ )-xanthoxylol, dihydrodehydrodiconiferyl alcohol, 3-methoxy-8,4'-oxyneoligna-3',4,7,9,9'-pentol, (8S)-3-methoxy-8,4'-oxyneoligna-3',4,9,9'-tetraol, (7S,8S)-3-methoxy-3',7-epoxy-8,4'-oxyneoligna-4,9,9'-triol and (7R,8S)-3-methoxy-3',7-epoxy-8,4'-oxyneoligna-4,9,9'-triol Fang et al, 1992 J. conferta -heartwood Savinin J. foetidissima -leaves Matairesinol, secoisolariciresinol J. nana -berries (- …”
Section: S2mentioning
confidence: 99%
“…In the last years a number of publications have reported the composition of the berries and leaves essential oil of the Juniperus species (Kallio and Junger-Mannermaa, 1989;Chatzopoulou and Katsiotis, 1993a;1993b;Koukos and Papadopoulou, 1997;Ochocka et al, 1997;Angioni et al, 2003;Milojevic et al, 2008;Orav et al, 2010). The chemical nature of juniper essential oil differs depending on its origin.…”
Section: Introductionmentioning
confidence: 99%